A new species of Costa Rican salamander, genus Bolitoglossa - Wake, David B. (1963)
A new species of salamander, Bolitoglossa epimela, is described from material collected between Turrialba and Peralta, Provincia de Cartago, Costa Rica. B. epimela is apparently most closely related to Bolitoglossa subpalmata, from which it differs in being smaller and slenderer with a narrower head, and having more fully webbed hands and feet. B. epimela apparently occurs at lower elevations than B. subpalmata.